2006
DOI: 10.3177/jnsv.52.70
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating Effect of Dimethylsulfoniopropionate on the 1-Methyl-4-phenyl-1,2,3,6-tetrahydropyridine-Induced Parkinson's Disease of Mice

Abstract: SummaryThe effect of dimethylsulfoniopropionate (DMSP) on the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine-induced Parkinson's disease (PD) of mice was examined for 5 d. The distilled water (the control group) and the DMSP solution at 5ϫ10 Ϫ4 M (the DMSP group) were supplemented ad libitum to six mice each in two groups for 2 wk. An appropriate amount of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) solution (20 mg/kg body wt) was then intraperitoneally injected into all the test mice once a day initiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Therefore, the obtained results may provide evidence that DMSP increases the amounts of catecholamines (17,19,22), and thus elevates the NGF amounts (40), which promotes the outgrowth and elongation of neurites from the nerve cells. These findings may suggest that DMSP, which directly incorporates and accumulates catecholamines into the livers and brains in the experiments with rats and mice (17,19,22), more effectively not only prevents and/or ameliorates the neuronal development from the retardation and denaturation of the central nervous system in a diseased brain (Alzheimer and Parkinson diseases) and the aging (especially dimentia) of humans, but also from various injuries of the peripheral and central nervous system in humans (28,41), accompanied by the increase of NGF.…”
Section: ϫ4mentioning
confidence: 69%
See 1 more Smart Citation
“…Therefore, the obtained results may provide evidence that DMSP increases the amounts of catecholamines (17,19,22), and thus elevates the NGF amounts (40), which promotes the outgrowth and elongation of neurites from the nerve cells. These findings may suggest that DMSP, which directly incorporates and accumulates catecholamines into the livers and brains in the experiments with rats and mice (17,19,22), more effectively not only prevents and/or ameliorates the neuronal development from the retardation and denaturation of the central nervous system in a diseased brain (Alzheimer and Parkinson diseases) and the aging (especially dimentia) of humans, but also from various injuries of the peripheral and central nervous system in humans (28,41), accompanied by the increase of NGF.…”
Section: ϫ4mentioning
confidence: 69%
“…In previous experiments, we examined the effects of the naturally-occurring sulfur-containing compound DMSP on various living things, which have interestingly demonstrated that this compound afforded favorable effects on the feeding, growth, motility, molting, metamorphosis and/or diseases of various plants ( 1 , 2 , 9 , 10 ) and animals (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) living in the water-and airenvironment among a number of related compounds. Among the DMSP effects, noticeable ameliorating effects of DMSP on the various aging phenomena, especially the loss of learning and memory, in the senescence-accelerated mouse (SAM) (23)(24)(25)(26) are believed to be very significant among them even at present and moreover in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Such reductions in wheel running reported in the present study may be due to depletion of central dopamine stores induced by repeated exposure to high doses of cocaine. Consistent with this possibility, a number of studies report that dopamine depletion induced by 6-hydroxydopamine lesions (Derevenco et al, 1986;Isobe and Nishino 2001), 1-methyl-4-phenyl-1,2,3,4-tetrahydropyridine lesions (Leng et al, 2004;Nakajima and Minematsu, 2006), and repeated amphetamine administration (Serwatkiewicz et al, 2000) markedly reduces exercise output in laboratory rats and mice.…”
Section: Discussionmentioning
confidence: 83%
“…The compound proves to rapidly incorporate into the livers and brains in rats and mice, stimulate their moving abilities and simultaneously accumulate large amounts of catecholamines in their viscera ( 9 , 10 ). We then examined the effects of DMSP on PD-model mice induced by 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) ( 11 ). The obtained results indicated that the supplementation of DMSP in PD-model mice induced by MPTP significantly recovers a characteristic symptom, especially immobility (Akinesia), of the mice, at which large amounts of dopamine and then norepinephline proved to accumulate in the brains of the mice except in the cerebellum ( 11 ).…”
mentioning
confidence: 99%
“…We then examined the effects of DMSP on PD-model mice induced by 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) ( 11 ). The obtained results indicated that the supplementation of DMSP in PD-model mice induced by MPTP significantly recovers a characteristic symptom, especially immobility (Akinesia), of the mice, at which large amounts of dopamine and then norepinephline proved to accumulate in the brains of the mice except in the cerebellum ( 11 ). We further attempted to examine the combined effects of DMSP with MPTP and nerve growth factor (NGF) on the outgrowth of neurites from nerve model cells, the rat adrenal pheochromocytoma (PC12) cells, which have been frequently used to examine various action mechanisms of the nerve cells and fibrils in the central nervous system in recent years ( 12 -14 ).…”
mentioning
confidence: 99%